Non-Inferior Efficacy of Tenofovir Disoproxil to Tenofovir Disoproxil Fumarate in Virologically Suppressed Chronic Hepatitis B Patients - Yim HJ; Kim JH; Cho YK; Kweon YO; Cho HC; Hwang JS; Lee C; Koh MS; Baek YH; Park YM; Lee JH; Kim SU; et al. (Dove Medical Press, 2022)
Hyung Joon Yim,1,* Ji Hoon Kim,2,* Yong Kyun Cho,3 Young Oh Kweon,4 Hyun Chin Cho,5 Jae Seok Hwang,6 Changhyeong Lee,7 Moon Soo Koh,8 Yang-Hyun Baek,9 Young-Min Park,10 Jeong-Hoon Lee,11 Seung Up Kim,12 Min-Kyu Kang,13 Neung Hwa Park,14 June Sung Lee,15 Young Eun Chon,16 Gab Jin Cheon,17 Hee Bok Chae,18 Joo Hyun Sohn,19 Young-Suk Lim20 1Department of Internal Medicine, Korea University Ansan Hospital, Korea University College of Medicine, Seoul, Korea; 2Department of Internal Medicine, Korea University Guro Hospital, Korea University College of Medicine, Seoul, Korea; 3Division of Gastroenterology and Hepatology, Department of Internal Medicine, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, Seoul, Korea; 4Department of Internal Medicine, Kyungpook National University, School of Medicine, Daegu, Korea; 5Department of Internal Medicine, Gyeongsang National University Hospital, Gyeongsang National University School of Medicine, Jinju, Korea; 6Department of Internal Medicine, Keimyung University School of Medicine, Daegu, Korea; 7Department of Internal Medicine, Daegu Catholic University School of Medicine, Daegu, Korea; 8Department of Internal Medicine, Dongguk University Ilsan Hospital, College of Medicine, Dongguk University, Goyang, Korea; 9Department of Gastroenterology, DongA University College of Medicine, Busan, Korea; 10Department of Internal Medicine, Bundang Jesaeng General Hospital, Seongnam, Korea and Hepatology Center, Bundang Jesaeng General Hospital, Seongnam, Korea; 11Department of Internal Medicine and Liver Research Institute, Seoul National University College of Medicine, Seoul, Korea; 12Department of Internal Medicine, Yonsei University College of Medicine, Seoul, Korea, and Yonsei Liver Center, Severance Hospital, Seoul, Korea; 13Department of Internal Medicine, Yeungnam University College of Medicine, Daegu, Korea; 14Department of Internal Medicine, Ulsan University Hospital, University of Ulsan College of Medicine, Ulsan, Korea; 15Department of Internal Medicine, Ilsan Paik Hospital, Inje University College of Medicine, Goyang, Korea; 16Department of Internal Medicine, CHA Bundang Medical Center, CHA University, Seongnam, Korea; 17Department of Medicine, GangNeung Asan Hospital, Ulsan University College of Medicine, Gangwon-do, Korea; 18Department of Internal Medicine, Chungbuk National University Hospital, Cheongju, Korea; 19Department of Internal Medicine, Hanyang University College of Medicine, Seoul, Korea, and Hanyang University Guri Hospital, Guri, Korea; 20Department of Gastroenterology, Liver Center, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Korea*These authors contributed equally to this workCorrespondence: Young-Suk Lim, Department of Gastroenterology, Liver Center, Asan Medical Center, University of Ulsan College of Medicine, 43-Gil 88, Olympic-Ro, Songpa-Gu, Seoul, Korea, Tel +82-2-3010-3190, Fax +82-2-485-5782, Email limys@amc.seoul.krPurpose: Tenofovir disoproxil (TD), modified from tenofovir disoproxil fumarate (TDF), was developed as a salt-free formulation, removing fumarate to improve the ease of oral intake by reducing the tablet's size. We evaluated the maintenance of antiviral effects and overall safety profile of TD 245 mg after switching from TDF 300 mg in patients with chronic hepatitis B (CHB).Patients and Methods: CHB patients with HBV-DNA < 69 IU/mL after ≥ 24 weeks of TDF therapy were enrolled. The primary efficacy endpoint was the HBV-DNA suppression rate (HBV-DNA < 69 IU/mL) at week 48; We evaluated the non-inferiority (10% margin) of TD to TDF in terms of efficacy. Safety was assessed based on adverse events (AEs), laboratory tests, bone mineral density, and renal function abnormalities.Results: Overall, 189 subjects were randomized in a 2:1 ratio, and 117 and 66 subjects in the TD and TDF groups, respectively, completed the study. In the per-protocol set, the HBV-DNA suppression rate at week 48 was 99.1% and 100% in the TD and TDF groups, respectively. The lower limit of the 97.5% one-sided confidence interval for the intergroup difference in HBV-DNA suppression rate was − 2.8%, which was greater than the prespecified margin of non-inferiority. The changes in creatinine clearance from baseline to week 48 was significantly less in the TD group and in the TDF group; − 0.8 ± 9.8 versus − 2.4 ± 12.8 mL/min, respectively (P=0.017).Conclusion: TD was non-inferior to TDF for maintaining viral suppression in CHB patients, showing the less decline of renal function.Keywords: viral DNA, bone density, antiviral agents, viral suppression